Analisis Sifat Kimia dan Fisika Lahan Gambut pada Areal Sekitar Laboratorium Terpadu Universitas Palangka Raya Kalimantan Tengah: Analysis of the Chemical and Physical Properties of Peatland in the Area Surrounding the Laboratorium Terpadu Palangka Raya University Central of Kalimantan - Trianingtyas, Andhira; Rahmawati, Reni; Putir, Patricia Erosa; Samad, Radhiatunnisa S; Putro, Dhymas Sulistyono; Hartati, Bunga Resa; Putra, Rizki Auliansyah (JURNAL HUTAN TROPIKA, 2025)
Peatlands are important ecosystems that play a crucial role in maintaining environmental balance, particularly in tropical regions such as Palangka Raya, Central of Kalimantan. This study aims to identify the physical and chemical characteristics of peat soils surrounding the Laboratorium Terpadu area at Palangka raya University, to support sustainable land management and campus environmental conservation. The results indicate that the peat soils at the site have a high water content (111.1%) and low bulk density (0.22 g/cm³), reflecting saturated, porous soil with a potential risk of subsidence if hydrological conditions are altered. Soil chemical properties show a pH of 4.3, indicating high acidity with low nutrient availability, and reflecting a relatively natural ecosystem. These physical and chemical characteristics have important implications for land use planning, vegetation cultivation, and campus spatial development, emphasizing the need for amelioration strategies, proper fertilization, and construction techniques that account for soil subsidence risks. This study provides a scientific basis for the wise and sustainable management of peatlands within the campus environment.